Laboratory observation of cracks in road pavements with GPR - Fernandes, Francisco M. (2017)
Cracks are one of the main distress mechanisms that affects the structural performance, comfort and durability of Hot Mix Asphalt (HMA) layers in road pavements. These cracks are generally of small size and can occur superficially, from top to bottom, from bottom to top, or they can run across the entire HMA layer thickness. Pavement rehabilitation is planned according to the bearing capacity of the pavement that is related to the number of cracks but also to its width (opening) and depth. Visible surface cracks can be manifested as superficial cracks or as cracks that already crossed the entire layer, and, both situations need different rehabilitation strategies. Therefore, there is an urgent need of accurate assessment of cracks characteristics to plan rehabilitation accordingly. Due to its characteristics useful for road inspection and high resolution, Ground Penetrating Radar (GPR) was used to assess its capability on detecting cracks of different widths. A laboratory experiment was setup to analyze the detectability of a crack in an asphalt slab (across the entire thickness) before and after a new slab was placed over the cracked one. The results showed that the possibility of the crack detection depends essentially on the contrast of the layers surrounding that crack. A numerical simulation was also performed and confirmed the experimental findings. It was also found that the amplitude of the reflected signal grows with crack width, contrarily to their shape, which remains fairly constant